CARTILAGE TISSUE ENGINEERING USING HUMAN ADIPOSE-DERIVED STEM CELLS INDUCED BY PLATELET RICH PLASMA AND CULTURED ON SILK FIBROIN SCAFFOLD - Rosadi, Imam
Microtia is a congenital malformation of the external ear caused by abnormal development and causing hearing loss. The malformation of microtia can be repaired by cartilage tissue engineering. Tissue engineering consists of cells, bioactive compound and scaffold. Research related to cartilage tissue engineering has been developed using cells cultured on natural or synthetic scaffolds. Type 2 collagen and aggrecan become markers of chondrogenesis and type 1 collagen as a marker of osteogenesis in stem cells chondrogenesis study. This research aims to generate cartilage tissue engineering from human adipose-derived stem cells (ADSC) that cultured on Bombyx mori silk fibroin scaffold supplemented by 10% platelet rich plasma (PRP). At first, we proved that we cultured ADSC from adipose tissue-derived isolated cells in this study by performing multipotency and specific cells-surface marker protein cluster of differentiation 73 (CD73), CD90, CD105 and CD34/CD45/CD11b/CD19 assays. Furthermore, ADSC was cultured on silk fibroin scaffold with 500 ?m pore size (ADSC-SS) supplemented by 10% PRP for 21 days to examine cells proliferation, chondrogenesis and osteogenesis differentiation, and expression of surface-marker protein on chondrogenic progenitor. The gene expression on messenger ribonucleic acid (mRNA) level of type 2 collagen, aggrecan and type 1 collagen were analyzed using reverse transcriptase-quantitative Polymerase Chain Reaction (RT-qPCR). The presence and abundance of type 2 collagen confirming chondrogenesis were proven by immunocytochemistry using rabbit anti-collagen II antibody (Abcam) observed by confocal microscopy. The negative and positive controls used in this study were ADSC-SS supplemented with 10% fetal bovine serum (FBS) and ADSC-SS supplemented with commercial chondrogenesis medium (StemPro, Gibco), respectively. This result showed that the cells from adipose tissue can be expanded and differentiated into adipocytes, chondrocytes and osteocytes. Cells expressed CD73 (99.97%), CD90 (99,89%), CD105 (97,25%) and CD34/CD45/CD11b/CD19 (0%) confirmed v the cells was ADSC. Proliferation of ADSC-SS PRP group was significantly increased compared to negative control on day 21. Chondrogenesis differentiation was observed in ADSC-SS PRP group which confirmed by increasing glycosaminoglycans (GAG) level, transforming growth factor-?1 (TGF-?1) secretion, and neither of mineral deposition or increasing of surface-marker protein on chondrogenic progenitor was occurred. The gene expression on mRNA level of type 2 collagen on ADSC-SS PRP group was increased and significantly different (p < 0.05) compared to negative control on day 7 and 21 and on day 14 with positive control. The gene expression on mRNA level of aggrecan on ADSC-SS PRP group was increased on day 14 and decreased until day 21 and significantly different (p < 0.01) to negative and positive controls on day 14. ADSC-SS on PRP group had stable mRNA expression level of type 1 collagen up to 14 days and was sharply decreased on day 21 and it was significantly different with negative control. The gene expression on mRNA level of type 1 collagen on ADSC-SS positive group was significantly higher compared to ADSC-SS PRP group on day 14. Although, the change of mRNA expression level of aggrecan on PRP group has similar trend with positive groups, mRNA expression level of positive control was higher than PRP group. The result of confocal analysis showed the presence of type 2 collagen on ADSC-SS positive and PRP groups on day 14 and 21. The presence of type 2 collagen was found outside the cells on ADSC-SS positive control group, but on ADSC-SS PRP group, it was also found in cytoplasm on day 14. The presence of type 2 collagen on ADSC-SS PRP and positive control groups were highly distributed outside the cells forming matrix extracellular on day 21. The gene expression on mRNA level of type 2 collagen on ADSC-SS PRP group detected on day 7 faster than the presence of type 2 collagen protein which detected on day 14 suggesting that the transcription and translation process probably did not occur directly on the same day. Higher gene expression on mRNA level and the abundance of collagen type 2 between ADSC-SS positive control and PRP groups on day 14 showed that chondrogenesis differentiation positive control was began faster than PRP. The results suggest that ADSC cultured on silk fibroin scaffold with 500 ?m pore size (ADSC-SS) were undergoing chondrogenesis differentiation with 10% PRP supplementation, therefore it was promising to be further develop as safer alternative for cartilage tissue engineering.